FAKTOR–FAKTOR PENENTU PRODUKSI PULP INDONESIA DENGAN PENDEKATAN FUNGSI PRODUKSI COBB-DOUGLASS - Firdayetti , (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2015)
The purpose of this studi is to evaluation and analysis influence of number of corporate, number of labor and total input to production of pulp in Indonesia. Using time series data collected period 2006 – 2013 and used regression model of Cobb Douglass Production Funftion, the result of this study shows number of corporate positives influenced to production of pulp but not significant. Number of labor positive significAnt influenced to production of pulp and total input positive significant influenced to production pulp. Another finding of this study shows that homogeneity of production of pulp in Indonesia is increasing return to scale althougt have value close to constan return to scale